Comparison of Carbamazipine and Amitryptyline for the Reduction of Diabetic Neuropathic Pain: A Randomized Clinical Trial - Rahman, MM; Khan, RK; Rizvi, N; M, Md Arifuzzaman; Sharif, A; Khanam, S (Bangladesh Journal of Neuroscience, 2017)
Background: Diabetic neuropathy is very difficult to treat. Objective: The purpose of the present study was to compare the efficacy and safety of carbamazepine and amitryptyline for reduction of diabetic neuropathic pain. Methodology: This was a randomized controlled trial conducted in the department of Neurology including Neuropathy Clinic of BSMMU and in collaboration with department of Endocrinology, BSMMU, Dhaka from January 2012 to December 2013 for a period of two (2) years. Adult diabetic patients presented with neuropathic pain with symmetrical involvement of distal limbs from indoor and outpatient department of Neurology including Neuropathy clinic as well as indoor and outpatient department of Endocrinology, BSMMU were enrolled in the study population. The study population was divided into two groups named as group A and group B. The group A was experimental group. In this group, patients were treated with oral carbamazepine 400mg/day in two divided doses for initial 2 weeks, then 600mg/ day in three divided doses for further 4 weeks. The group B was control group. In this group, patients were treated with oral amitriptyline 25mg/ day at night for initial 2 weeks, then 50mg/day taking at night for further 4 weeks. During trial, three follow ups were taken at 2 weeks interval and encountered the clinical response by pain score (VAS) and the side effects. The first follow up after 2 weeks of treatment; the second follow up was after 4 weeks of treatment and the third follow up was after 6 weeks of treatment. Result: A total number of 110 cases clinically diagnosed as painful diabetic polyneuropathy, then 56 cases randomly selected for Group A and 54 cases randomly selected for Group B. During follow up of 6 weeks, 2 case of Group A developed skin rash for which they discontinued drug. From rest of cases, 2 from Group A and 4 from Group B were dropped out. Because they did not come for follow up. So finally 52 cases for Group A group and 50 cases for Group B group were studied. A total of 102 patients were included in the study. They were divided into four Groups according to their age. The mean age was found 52.17(±10.02) years in Group A and 53.41(±8.82) years in Group B. The mean (±SD) of percent improvement in Group A and Group B were 41.11(±11.29) vs. 31.76(±19.14) (P<0.05). Dizziness and Drowsiness were found in Group A as 33.3% and 37.0%. But in Group B dryness of mouth and constipation were found as 46.3% and 7.4%. Conclusion: In conclusion carbamazepine produced greater improvements than amitriptyline in relieving pain and paresthesia associated with diabetic neuropathy. Bangladesh Journal of Neuroscience 2017; Vol. 33 (1): 6-12